2020
DOI: 10.1080/1536383x.2020.1757656
|View full text |Cite
|
Sign up to set email alerts
|

Study of cytotoxicity performance of carbon nanohorns by method of spin probes

Abstract: Study of cytotoxicity performance of carbon nanohorns by method of spin probes. (2020) Fullerenes Nanotubes and Carbon Nanostructures, 28 (9). 1-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As the toluene content increases from 2.4 to 8.0 mL, the intensities of these peaks increase significantly. The spectra of oxidized CNHs reveal enhancement of the intensity of the O–H, C–O and C=O stretching bands indicating functionalization of nanohorns with hydroxyl and carboxyl groups and the presence of adsorbed water molecules [ 16 ]. The new peaks appeared between 1630 and 1690 cm −1 could be related to the oscillation of O–H bands or to the C=O stretching bands of quinone groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the toluene content increases from 2.4 to 8.0 mL, the intensities of these peaks increase significantly. The spectra of oxidized CNHs reveal enhancement of the intensity of the O–H, C–O and C=O stretching bands indicating functionalization of nanohorns with hydroxyl and carboxyl groups and the presence of adsorbed water molecules [ 16 ]. The new peaks appeared between 1630 and 1690 cm −1 could be related to the oscillation of O–H bands or to the C=O stretching bands of quinone groups.…”
Section: Resultsmentioning
confidence: 99%
“…During the synthesis, the CNHs are combined into spherical particles, which can form large van der Waals associates [ 1 , 2 , 3 , 4 , 5 ]. High pore volume [ 6 , 7 , 8 ] and specific surface area (SSA) [ 9 , 10 ] make CNHs very promising for nanofluids [ 11 , 12 ], catalysis [ 13 , 14 ], medicine [ 15 , 16 , 17 , 18 ], electrochemistry [ 9 , 19 ], electromagnetic [ 2 , 5 , 20 ] and sensing applications [ 6 , 21 , 22 ]. In this regard, the improvement of availability of their pores for guest species, the increase of the SSA value, and the enhancement of the stability of their suspensions become very important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies on the toxicity of C60 in vitro, increasing the concentration of fullerenes to 36 mg/mL will result in a 20% reduction in the viability of HEK293 cells [22], and that fullerene C60 has a low toxicity to HEK293 cells with an estimated IC50 value of 383.4 lg/mL.…”
Section: Fullerenes Toxicitymentioning
confidence: 99%
“…The study conducted by He et al 8 also indicated that the internalization of CNH in macrophages via phagocytosis presented a lower membrane disturbance compared to CNT. Based on the electron paramagnetic resonance (EPR) spectra using a spin probe technique, Kartel et al 22 described that the interaction of CNHox with erythrocytes of rats caused disorders in the outer leaflet of the lipid bilayers, as well as an increase of polarity in this microenvironment.…”
Section: Introductionmentioning
confidence: 99%